Drivers of Change: Sovereign Wealth - Capapé, Javier (IE Fundation, 2019)
Drafted with the participation of internationally renowned experts, the 2018 Sovereign Wealth Funds Report analyses the most recent trends in the SWFs industry, including new and consolidated funds, largest deals and top sectors targeted, such as consumer, real estate, chemicals and energy. The period 2017-2018 marked an all-time-record of SWFs activity on venture capital-backed startups. Geographically, countries like the USA, China and India remain as top destinations for SWFs. Also, the Report covers in depth the changes in strategic asset allocation made by SWFs over the last decade, and the renewed push on co-investing with other global financial players, showing maturity and sophistication.
Keywords: Sovereign wealth funds; Investments; Strategy; Risks; Spain; Economy